Antiulcerous Efficacy of Reamberin at the Background of the Stress Ulcerogenic Factor Action - O. P. Rodina; I. Ya. Moiseeva (Антибиотики и Химиотерапия)
The effect of reamberin on morphofunctional changes in the small intestine mucous membrane due to stress ulcerogenesis was studied. Normalization of the lipid modifications in the tissue structure, evident of the drug antiulcerous properties, was observed.